2021
DOI: 10.3389/fneur.2021.661689
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Glucose to Potassium Ratio and Mortality After Aneurysmal Subarachnoid Hemorrhage

Abstract: Objectives: Hyperglycemia and hypokalemia are common problems in patients with aneurysmal subarachnoid hemorrhage (aSAH). The aim of this study was to determine whether the plasma glucose to potassium ratio (GPR) predicts mortality due to aSAH.Methods: We prospectively recruited aSAH patients and healthy controls between March 2007 and May 2017. Clinical outcomes included mortality and poor outcome (modified Rankin scale score of 3-6) after 3 months. Multivariable analysis was used to determine the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Previous literature reported that higher serum GPR level at admission was significantly associated with poor outcome or mortality at 3 months following aSAH ( 17 , 18 ). However, the studies fail to answer whether the GPR levels are related to early brain injury risk.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous literature reported that higher serum GPR level at admission was significantly associated with poor outcome or mortality at 3 months following aSAH ( 17 , 18 ). However, the studies fail to answer whether the GPR levels are related to early brain injury risk.…”
Section: Discussionmentioning
confidence: 90%
“…Associations of elevated GPR levels with poor outcome and mortality have been described in patients with aSAH ( 17 , 18 ) but never concerning rebleeding occurrence. How can elevated GPR levels (increased blood glucose and decreased potassium) cause rebleeding?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between admission hyperglycemia and mortality was also extensively analyzed; Bian et al demonstrated that admission BG was associated with 1-year mortality after being adjusted for other confounding factors in a study including 239 SAH patients (17). Another study from South Korea including 553 SAH patients found that BG at admission was not an independent predictor for 3-month mortality, although BG level was significantly higher in non-survivors and patients with poor outcome (18). Incidentally, there were also studies suggesting that admission hyperglycemia predicted short-term (30 days), but not long-term, mortality in SAH patients (19).…”
Section: Introductionmentioning
confidence: 99%